Max Plus Algebra Application In Air Defence Systems - Zumrotus Sya'diyah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2025)
Air defence is one of the vital systems in national defence. This system generally includes several processes, namely detection by radar, object identification and decision making. The level of success really depends on the accuracy of decision-making. However, it is not yet known for certain which processes critical processes in decision-making. In this research, we will discuss the application of max plus algebra in determining which process of the workflow for air defence systems is the most critical one. Graphical interpretation of the system using graphs and Timed Petri Nets to make it easier to understand and analyse. The research results show that the success of the entire process depends on the readiness of the radar in carrying out surveillance of the coverage area. This can be seen from the critical circuit, which only depends on the place relating to the situation. Keywords: Max plus algebra, Timed Petri Net, air defence system.